2021
DOI: 10.1007/s10479-021-04155-4
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain vulnerability assessment for manufacturing industry

Abstract: In today's business, environment natural and manmade disasters like recent event (Covid 19) have increased the attention of practitioners and researchers to Supply chain vulnerability. Purpose of this paper is to investigate and prioritize the factors that are responsible for supply chain vulnerability. Extant literature review and interviews with the experts helped to extract 26 supply chain vulnerability factors. Further, the relative criticality of vulnerability factors is assessed by analytical hierarchy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…These disruptions may occur at one level of a supply chain and quickly propagate to the entire supply chain or even other supply chains (Samvedi et al, 2013 ). The critical impacts of disruptions on supply chains’ performance stimulate researchers to put focus on SCRM/supply chain disruption management and identify a wide range of risks (Sharma, 2021a ; Wagner & Bode, 2008 ; Xie, 2011 ). Those risks mainly occur due to natural disasters like tsunami, earthquake, bushfires or man-made disasters, such as sanctions, war, oil spills and terrorist attacks (Chopra & Sodhi, 2004 ; Ho et al, 2015 ; Jüttner et al, 2003 ; Sodhi et al, 2012 ; Thun & Hoenig, 2011 ; Xie, 2011 ).…”
Section: Survey On the Literaturementioning
confidence: 99%
“…These disruptions may occur at one level of a supply chain and quickly propagate to the entire supply chain or even other supply chains (Samvedi et al, 2013 ). The critical impacts of disruptions on supply chains’ performance stimulate researchers to put focus on SCRM/supply chain disruption management and identify a wide range of risks (Sharma, 2021a ; Wagner & Bode, 2008 ; Xie, 2011 ). Those risks mainly occur due to natural disasters like tsunami, earthquake, bushfires or man-made disasters, such as sanctions, war, oil spills and terrorist attacks (Chopra & Sodhi, 2004 ; Ho et al, 2015 ; Jüttner et al, 2003 ; Sodhi et al, 2012 ; Thun & Hoenig, 2011 ; Xie, 2011 ).…”
Section: Survey On the Literaturementioning
confidence: 99%
“…Fraudsters used either public transport or their own supply chain company to move this product and sell it into the market under the brand and label of the more expensive one. Lack of transparency in the supply chain and low integration levels across the supply chain (SSAFE, 2016) had increased supply chain vulnerabilities (Sharma et al. , 2021), leading to these fraudulent activities.…”
Section: Resultsmentioning
confidence: 99%
“…Fraudsters used either public transport or their own supply chain company to move this product and sell it into the market under the brand and label of the more expensive one. Lack of transparency in the supply chain and low integration levels across the supply chain (SSAFE, 2016) had increased supply chain vulnerabilities (Sharma et al, 2021), leading to these fraudulent activities. Most incidents related to this insight originated from India, where successful detection of these cases resulted from ad hoc midnight raids of unregistered houses that were used for the fraudulent activities to avoid detection in the first place.…”
Section: Identifying Food Fraud Vulnerability Factorsmentioning
confidence: 99%
“…Ruel et al [18] observed an increase in the complexity and vulnerability of their supply chains as a result of global networks and a turbulent environment. Sharma et al [19] investigated and prioritized the factors that are responsible for supply chain vulnerability. Parast and Subramanian [20] examined the relationship of supply chain disruption risk drivers and firm performance.…”
Section: Theory Of Supply Chain Resiliencementioning
confidence: 99%